Insurgency And Credible Commitment In Autocracies And Democracies - Keefer, Philip (The World Bank, 2007)
This paper suggests a new factor that makes civil war more likely: the inability of political actors to make credible promises to broad segments of society. Lacking this ability, both elected and unelected governments pursue public policies that leave citizens less well-off and more prone to revolt. At the same time, these actors have a reduced ability to build an anti-insurgency capacity in the first place, since they are less able to prevent anti-insurgents from themselves mounting coups. But while reducing the risk of conflict overall, increasing credibility can, over some range, worsen the effects of natural resources and ethnic fragmentation on civil war. Empirical tests using various measures of political credibility support these conclusions